2003
DOI: 10.1590/s0036-46652003000500007
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis: relationship between sputum bacilloscopy and radiological lesions

Abstract: Parenchymal-infiltrate lesions are the most frequent radiological manifestation of pulmonary tuberculosis, and they are generally associated with cavities. There is a relationship between the presence of acid fast bacilli in sputum and pulmonary cavity lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
(46 reference statements)
0
17
0
7
Order By: Relevance
“…Chest X-rays with an anteroposterior view were obtained and temporally related sputum samples were collected for bacilloscopic study or culture [33,34]. Imaging methods were also used for diagnosis of the clinical form of TB [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Chest X-rays with an anteroposterior view were obtained and temporally related sputum samples were collected for bacilloscopic study or culture [33,34]. Imaging methods were also used for diagnosis of the clinical form of TB [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of cavitary disease on chest radiograph at the time of diagnosis also is a strong predictor of relapse after treatment (9)(10)(11)(12)(13)(14). The proportion of adults with newly diagnosed TB who have cavitary disease ranges from 40 to 87% (15)(16)(17). Patients …”
mentioning
confidence: 99%
“…The proportion of adults with pulmonary tuberculosis (TB) who have cavitary disease at the time of diagnosis ranges from 40 to 87% (1,9,17). Several studies using qualitative smears and cultures have shown that patients with cavitary pulmonary TB have higher bacterial loads in their sputum (3,9,10,12,15).…”
mentioning
confidence: 99%
“…Several studies using qualitative smears and cultures have shown that patients with cavitary pulmonary TB have higher bacterial loads in their sputum (3,9,10,12,15). In 1965, Canetti and Grosset compared bacillary load in lung sections from resected lung tissue in patients with pulmonary TB.…”
mentioning
confidence: 99%